Design of Water Heater Temperature Control System using PID Control - Rahmadini, Vatia Fahrunisa; Ma'arif, Alfian; Abu, Nur Syuhadah (Peneliti Teknologi Teknik Indonesia, 2023)
This research delves into advanced control methodologies by investigating the intricate applications of Proportional-Integral-Derivative (PID) control for achieving precise and dependable temperature regulation within electric water heaters. The study delves into various control strategies, namely Proportional, Proportional-Integral, and Proportional-Integral-Derivative methodologies, to realize the pinnacle of stable and exacting temperature control. The Proportional Controller, operating with a Kp value of 10, stands out with its relentless performance, characterized by minimal overshoot and an inconsequential steady-state error. Implementing the Proportional-Integral Controller, synergizing Kp at 10 and Ki at 5, elevates system stability while deftly curbing any hint of overshoot. The dynamic interplay between the Kp, Ki, and Kd parameters in the Proportional-Integral-Derivative (PID) Controller unveils an intricate dance of precision and control. Notably, configurations involving Kp 10, Ki 5, and Kd 2 emerge as beacons of rapid stabilization, heightened precision, and masterful overshoot management, exemplified by a rise time of 119.3543 seconds, settling time of 162.6116 seconds, overshoot of 1.0299%, peak time of 216 seconds, and a commendably low steady-state error of 0.31. This extensive exploration bears testament to its instrumental role in optimizing PID control strategies, ushering in augmented efficacy and pinpoint accuracy in water temperature regulation across an expansive spectrum of applications. As a result, these findings pave the way for the evolution of control methodologies that transcend theoretical confines and manifest within practical scenarios with profound impact.